Utilization of palm oil sludge through pyrolysis for bio-oil and bio-char production - Thangalazhy-Gopakumar, S.; Al-Nadheri, W.M.A.; Jegarajan, D.; Sahu, J.N.; Mubarak, N.M.; Nizamuddin, S. (Elsevier, 2015)
In this study, pyrolysis technique was utilized for converting palm oil sludge to value added materials: bio-oil (liquid fuel) and bio-char (soil amendment). The bio-oil yield obtained was 27.4 +/- 1.7 wt. having a heating value of 22.2 +/- 3.7 MJ/kg and a negligible ash content of 0.23 +/- 0.01 wt.. The pH of bio-oil was in alkaline region. The bio-char yielded 49.9 +/- 0.3 wt., which was further investigated for sorption efficiency by adsorbing metal (Cd2+ ions) from water. The removal efficiency of Cd2+ was 89.4 +/- 2, which was almost similar to the removal efficiency of a commercial activated carbon. The adsorption isotherm was well described by Langmuir model. Therefore, pyrolysis is proved as an efficient tool for palm oil sludge management, where the waste was converted into valuable products.